PREPARASI MEMBRAN KOMPLEKS POLIELEKTROLIT KITOSAN/ Îº-KARAGINAN DAN APLIKASINYA UNTUK TRANSPOR KREATININ - , DIAN YUSTITIA, Dr. Dwi Siswanta, M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Chitosan/Îº-carrageenan polyelectrolyte complex (PEC) me mbrane has been synthesized and used for creatinine transport. The chitosan/Îº-carrageenan PEC membrane were prepared from the interaction between the positively charged of chitosan (âNH 3 + ) and the negatively charged Îº-carrageenan (âOSO 3 -) at 3 various ratios of composition, e.g. 40:60